Profil Tingkat Kenyamanan Udara dan Hubungannya Dengan Hari Hujan di Bukit Kototabang Tahun 2010-2018 - Sulistiyono, Andi; Davi, Rendi Septa; Arifin, Ikhsan Buyung (Megasains, 2020)
The change of the environment around the station of Global Atmospheric Watch Bukit Kototabang allegedly causing change in the weather factors that affect the level of discomfort. This study aims to determine the level of comfort at Bukit Kototabang GAW station and its relationship to rainy days. Study of discomfort level using calculation of Humidex was conducted using diurnal AAWS data and Fklim data resulted that does not occur "Uncomfortable" conditions for the period 2010-2018. The conditions are "Comfortable" in the morning and evening periods while in the afternoon the conditions are " Less Comfortableâ€. The largest percentage of " Comfortable " days occur in July and January. The percentage of " Comfortable â€œ days for 2013-2015 is lower compared to the year before (2010-2013) and the year after (2016-2018). There is no decrease in the percentage of "Comfortable" in 2017-2018 against previous years, then it is considered that there is no effect of comfort levels for 2017-2018 on changes in the environment around the station..The correlation of " Comfortable" days to monthly rainy days during study period is 0.69, but the number of monthly rainy days (rain events) is less appreciative of the number of days of "Comfortable" conditions at GAW Bukit Kototabang Station